From Competing Institutional Logics to the Action Horizons of Mediatised Political Performance: A New Approach to the Relationship between Media and Political Action - Kumpu, Ville; Kunelius, Risto; Reunanen, Esa (Javnost-The Public, 2019)
This article introduces a new approach aimed at capturing three essential action horizons of mediatised political action. The proposed approach focuses on how institutional, discursive and argumentative horizons come together to form a historically specific and issue-dependent publicity that influences how political actors communicate their power and aims. We argue that by studying the interplay of these three horizons in different times and contexts, we can better understand the media’s changing role in politics than by focusing only on the alleged characteristics of media logic (e.g. personalisation and negativism), often proposed in the debates about mediatisation and media interventionism.